SUMBANGSIH PESANTREN DALAM HISTORIOGRAFI NUSANTARA SEBUAH KAJIAN PENDIDIKAN ISLAM - Jasminto, Jasminto (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
Pesantren as an Islamic educational institution in Indonesia has a meaning and role that is very urgent in order to improve the standard of living and maintain tolerance in a diverse society. The journey of pesantren as an institution that concentrates on the field of education requires mutual attention. The existence of Pesantren is the mandate of the nation, even before the independence of Indonesia, while its implementation at the moment is the implementation of the joint responsibility in accordance with the mandate in the Preamble of the 1945 Constitution of paragraph IV and Article 31 of the 1945 Constitution. The development in Indonesia is carried out by various institutions education both general education and Islamic education that has a different background. The Pesantren as an Islamic educational institution that is built and developed in Indonesia is one type of Islamic education of Indonesia that is both traditional and modern to deepen the knowledge of Islam, live in society and nation. Historically, the development of pesantren in Indonesia has different backgrounds, styles and roles, as well as the struggle to realize national educational goals framed in Islamic religious education. Thus, in this study will be discussed a brief history of Islamic boarding schools, Islamic education in Indonesia as well as about pesantren as educational institutions that have a characteristic nationality.